HUBUNGAN KEBIASAAN SARAPAN DAN PERAN ORANG TUA DALAM MENDORONG MAKANAN SEHAT TERHADAP STATUS BERAT BADAN PADA REMAJA DI MTS HASYIM ASY’ARI BANGSRI JEPARA - Amelia Dwi Agustin; Diana Tri Lestari; Muhammad Purnomo (Nusantara Hasana Journal, 2026)
This study aims to determine the relationship between breakfast habits and the role of parents in encouraging healthy food consumption with weight status in adolescents at MTs Hasyim Asy'ari Bangsri Jepara. This study was conducted because adolescents are vulnerable to nutritional problems due to irregular eating patterns, the habit of skipping breakfast, and lack of family support in establishing healthy eating patterns. The study used an observational analytical method with a cross-sectional approach. The research sample was selected using a proportional random sampling technique. The independent variables in this study were breakfast habits and the role of parents in encouraging healthy food consumption, while the dependent variable was the adolescents' weight status. Data collection was carried out using questionnaires and weight and height measurements to determine BMI/U based on WHO standards. The results showed that the majority of respondents were female (64.7%) and most were 14 years old. The results of the Chi-Square test showed a significant relationship between breakfast habits and weight status in adolescents with a p-value of 0.001 (p<0.05). Furthermore, there was a significant correlation between parental involvement in encouraging healthy food consumption and weight status in adolescents, with a p-value of 0.000 (p<0.05). The study concluded that breakfast habits and parental involvement were significantly associated with weight status in adolescents.